Increased climate resilience an imperative for Asian Mega Deltas - Asian Development Bank (Economist, 2025)
The article, published by the Asian Development Bank (ADB), argues that climate-proofing Asia's mega-deltas is imperative as these regions, home to over 400 million people, face an existential threat from climate change and unsustainable human activities. It stresses the urgent need to move beyond traditional engineering solutions by adopting nature-based solutions, implementing integrated governance, and promoting climate-resilient agricultural practices to ensure long-term food and economic security.